2022
DOI: 10.1021/acs.energyfuels.1c03369
|View full text |Cite
|
Sign up to set email alerts
|

Review on Self-Heating of Biomass Materials: Understanding and Description

Abstract: Storage of bulk biomass materials is essential along the feedstock supply chain of bioenergy production. The self-heating accompanying biomass storage has hazardous consequences. With the increasing biomass utilization for bioenergy production, the risk and economic and environmental concerns about biomass storage have been attracting extensive research attention aimed at understanding the processes of heat generation, evaluating the propensity of a material to self-heating and spontaneous ignition, describing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 255 publications
1
16
0
Order By: Relevance
“…Rattanachomsrim, however, reported that Firmicutes were abundant in 3-month-old bagasse whose temperature was ~50°C. This suggests that the latter was still in the thermophilic phase of composting [ 29 , 30 ], which is consistent with the work of Gebbie et al who recently reported resampling the same undisturbed bagasse pile (~ 8 months apart) at multiple depths [ 26 ]. Not surprisingly, they found differences in both bacterial and fungal communities with depth and time.…”
Section: Discussionsupporting
confidence: 83%
“…Rattanachomsrim, however, reported that Firmicutes were abundant in 3-month-old bagasse whose temperature was ~50°C. This suggests that the latter was still in the thermophilic phase of composting [ 29 , 30 ], which is consistent with the work of Gebbie et al who recently reported resampling the same undisturbed bagasse pile (~ 8 months apart) at multiple depths [ 26 ]. Not surprisingly, they found differences in both bacterial and fungal communities with depth and time.…”
Section: Discussionsupporting
confidence: 83%
“…Different authors recommended up to 15% moisture for most biomass to maintain a stable process since feedstocks with high moisture reduce the temperature of the reactor and slow down some endothermic reactions. 6 In addition, feedstocks with high moisture contents might cause fluidization issues in fluidizedbed reactors and large coking due to temperature oscillations within the gasifier caused by a high moisture content. 102 Therefore, biomass should be dried to a specified technological limit to enhance the energy output of biomass−plastic cogasification.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Excessive moisture content typically decreases process efficiency while increasing tar production. Different authors recommended up to 15% moisture for most biomass to maintain a stable process since feedstocks with high moisture reduce the temperature of the reactor and slow down some endothermic reactions . In addition, feedstocks with high moisture contents might cause fluidization issues in fluidized-bed reactors and large coking due to temperature oscillations within the gasifier caused by a high moisture content .…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most biomass raw materials have two typical structural features: (a) versatile and repeated polar units and (b) ubiquitous inter/intramolecular hydrogen bonds. 27–29 These natural assembly characteristics in biomass structures have been mimicked and used to construct artificial systems, with polar monomers and hydrogen bonding as the building blocks and driving force, respectively. 30,31 The obtained progresses inspired and encouraged us to convert biomass into functional materials via a supramolecular approach.…”
Section: Introductionmentioning
confidence: 99%